VD_FINDINFO Arrêt / 2011 / 856 vom 16. Februar 2012 - VD Tribunal cantonal (2012)
DEGRÉ DE L'INVALIDITÉ, INVALIDITÉINFIRMITÉ, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 4 LAI, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 LPGA